PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 74 PEKANBARU - Suci Juita Sari; Gustimal Witri; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the fact that is found in the class V Elementary School 74 Pekanbaru, which shows the result of learning mathematic is still relatively low. The purpose of this research to improve learning outcomes of mathematic fifth grade students of SDN 74 Pekanbaru with the application of cooperative learning model Team Assisted Individualization (TAI) type. The hypothesis of this study is that if applied cooperative learning model Team Assisted Individualization (TAI) type it can improve learning outcomes fifth grade students of SDN 74 Pekanbaru. This research was conducted in the class VB SDN 74 Pekanbaru in March to April , 2016. The subjects were students of class V Elementary School 74 Pekanbaru which amounted to 33 people consisting of 19 men and 14 woman. This form of reseacrh is classroom action reasearch (PTK) are planned as much as two cycles. The data in this research is quantitative derived from the teacher activity sheet, students activity sheet and student learning outcomes data through daily test also. Based on the results of research of teacher activity sheet seen rising each meeting. At the frst meeting of the first cycle of 70%, the second meeting rise 77,5%. In the first meeting of the second cycle of 87,5% then at the second meeting increase to 92,5%. Student activity observation sheet also increased at every meeting. At the first meeting of the first cycle of 67,5%, the second meeting increase to 72,5%. While in the fist meeting of the second cycle of 85%, then at the second meeting increase to 90%. Mathematic learning outcomes has increased from an average value base score to UH I increased by 30.4 % with an average value of UH I 84.69 ( 84.84% complete category ). UH II on the average increased to 86.69 with the percentage increase of 33.51% (90.90% complete category). So that research result are consistent with the hypothesis.Key Words: Cooperative learning model team assisted individualization (TAI) type,learningoutcomes